Some coagulase negative Staphylococcus spp. isolated from buffalo can be misidentified as Staphylococcus aureus by phenotypic and Sa442 PCR methods - De Almeida, Camila C. [UNESP]; Pizauro, Lucas J. L. [UNESP]; Soltes, Glenn A.; Slavic, Durda; De Ávila, Fernando A. [UNESP]; Pizauro, João M. [UNESP]; MacInnes, Janet I. (Springer Nature, 2018)
Objective: Staphylococcus aureus is a commonly reported cause of buffalo mastitis. However, its prevalence may be overestimated. The aim of this study was to compare S. aureus identification by conventional phenotypic and genotypic assays versus Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry (MALDI-TOF MS) and novel real-time quantitative PCR tests for the cytochrome oxidase subunit D II (cydB) and staphylocoagulase (coa) genes. Results: From 408 samples obtained from buffalo milk/milking environment, 32 putative S. aureus strains were identified based on characteristic growth on Baird Parker agar, positive catalase reaction, ability to clot rabbit plasma, and positive Sa442 PCR assay. However, in further testing, only 10 of these strains were positive in latex agglutination tests and by MALDI-TOF MS, only eight of the 32 strains were S. aureus while the rest were S. chromogenes (19), S. agnetis (3), S. cohnii (1), or S. xylosus (1). All eight strains identified as S. aureus by MALDI-TOF analysis and confirmed by 16S RNA gene sequencing were positive in a S. aureus-specific cydB PCR test. As well, 7/8 S. aureus strains were PCR positive in a real-time coa PCR test as were 2/69 S. chromogenes and the lone S. xylosus strain tested.
Keywords: cydB PCR; Mastitis; Species-specific PCR tests; Staphylococcus aureus